HUBUNGAN KARAKTERISTIK PEKERJA DAN CARA KERJA DENGAN KELELAHAN KERJA PADA PEMANEN KELAPA SAWIT DI PT. PERKEBUNAN NUSANTARA IV (PERSERO) UNIT USAHA ADOLINA TAHUN 2012 - Annisa Mentari; Kalsum .; Umi Salmah (Lingkungan dan Kesehatan Kerja, 2012)
Relationship between worker characteristics and how to work with fatigue conducted by oil palm harvester in PT. Perkebunan Nusantara IV (Persero) Unit Usaha Adolina 2012.. Physical activity of the oil palm harvester work in PT. Perkebunan Nusantara IV (Persero) Unit Usaha Adolina as a whole was still done manually is risk to experienInterval Kepercayaanng fatigue. This research was an analytic researching with cross sectional design toanalyze the relationship between worker characteristics and how to work with fatigue caused by harvesting conducted by oil palm harvester in PT. Perkebunan Nusantara IV (Persero) Unit Usaha Adolina 2012. This research was carried out in PT Perkebunan Nusantara IV Unit Usaha Adolina Kab. Serdang Berdagai,which the number of sample were 81 harvesters.The result of this research showed that there are relationship between age with fatigue (p=0.002), there is relationship between history of disease with fatigue (p=0.001), there is relationship between the period of work with fatigue (p=0.009), there is relationship between nutritional status with fatigue (p=0.016), there is a significant relationship between the how of working to cut stem and TBS according to the different age of the plant with fatigue (p=0.001). there was no significant relationship between the how of working to lift, entering, and carrying TBS with use rickshaw to TPH according to the different age of the plant with fatigue (p=0.238).From the result of the study suggested to the management, to adjust the number of harvesters to harvest a different way of working according to the age plant, due to the distinct level of difficulty and also the expense. Key words: fatigue, harvester, Adolina.